Pandemic-Based Stress and Timing of Fertility Intentions among Partnered Adults - Wendy D. Manning; Karen Benjamin Guzzo; Claire Kamp Dush; Gabrielle Juteau (Socius)
Despite initial declines in fertility since the onset of the pandemic, less is known about how fertility intentions are related to pandemic-based stressors in the United States. The authors examine the following two questions. First, how are pandemic stressors associated with short-term fertility intentions? Second, among those delaying fertility, what are the rationales for doing so, and how are pandemic stressors related to these rationales? The authors draw on the National Couples’ Health and Time Study, a nationally representative sample of 20- to 50-year-olds in the United States who were married or cohabiting and interviewed between September 2020 and April 2021. Among those desiring or remaining open to having (more) children, experiencing pandemic-related stressors was associated with delays in fertility plans; those whose lives were most disrupted and those who experienced relationship stress were less likely to intend to have children in the next year. The most common rationale for not intending to have children in the next year was economic worries, followed by health worries and concerns about an uncertain future. Economic and health stress were linked to these rationales, net of objective indicators. A comprehensive assessment of fertility intentions and underlying rationale for intentions on the basis of subjective factors is critical for understanding fertility patterns.